Is surgical myectomy challenged by emergence of novel drug therapy with mavacamten?. (January 2022) - Maron, Martin S; Rowin, Ethan J; Maron, Barry J
For 60 years, surgical myectomy has been the definitive treatment for symptomatic obstructive hypertrophic cardiomyopathy (HCM). Myectomy provides the opportunity to reverse heart failure symptoms in the vast majority of patient with low risk when performed in experienced centers and associated with extended longevity. More recently, a novel class of negative inotropic drug therapy with mavacamten has emerged offering expanded treatment options for obstructive HCM. In the recently completed phase III clinical trial, the EXPLORER-HCM about one-third of patients on mavacamten achieved the primary end-point of subjective symptomatic improvement and increased functional capacity assessed by peak VO2 . Of note, outflow gradients persistent in 43% of patients on mavacamten and 50% with symptoms consistent with NYHA class II or greater. A subset of patients also experienced significant reversible systolic dysfunction. Therefore, it is timely to place into perspective the potential role of mavacamten in context of the established low risk: high benefit of surgical myectomy for treatment of heart failure.